Exercise intensity and its effects on thyroid hormones - Ciloglu, F; Peker, I; Pehlivan, A; Karacabey, K; Ilhan, N; Saygin, O; Ozmerdivenli, R (Maghira & Maas Publications, 2005)
BACKGROUND: Physical activity influences energy metabolism inhuman subjects by increasing activity-induced energy expenditure and resting metabolic rate for several hours after exercise. Effects of exercise on circulating thyroid hormone values remain controversial. We have investigated the effect of acute aerobic exercise on thyroid hormone values. MATERIALS/METHODS: The effect of different intensity levels of acute aerobic exercise on thyroid hormones was investigated in 60 male well-trained athletes by performing bicycle ergometer at 45% (low intensity), 70% (moderate intensity), and 90% (high intensity). These intensities were selected according to their maximum heart rate (MHR). At each intensity level, heart rate, blood lactic acid, serum total thyroxine (T4), free thyroxine (fT4), total triiodothyronine (T3), free triiodothyronine (fT3) and thyroid stimulating hormone (TSH) values were measured. RESULTS: The results of this study show that exercise performed at the anaerobic threshold (70% of maximum heart rate, lactate level 4.59 +/- 1.75 mmol/l) caused the most prominent changes in the amount of any hormone values. While the rate of T4, fT4, and TSH continued to rise at 90% of maximum heart rate, the rate of T3 and fT3 started to fall. CONCLUSIONS: Maximal aerobic exercise greatly affects the level of circulating thyroid hormones.
Keywords: exercise; thyroid hormone; thyroxine